Estimation of equivalent stresses and equivalents of the fatigue test programs of airframe composite elements - V. E. Strizhius (Научный вестник МГТУ ГА)
It is known that for metal components of aircraft structures, "equivalent stress" is one of the most important parameters used to assess the fatigue damage resistance of a structural element for a given program of its fatigue tests. The method and the procedure for estimating the values of this parameter for metal elements of aircraft structures are presented It is noted that for aircraft structural elements made of polymer composite materials, neither the concept of the "equivalent stress" parameter nor the methods for calculating estimates of the values of this parameter are currently defined in domestic and foreign studies of the fatigue strength of such elements. In order to achieve particular progress in the considered area, the definition of the "equivalent stress" parameter of fatigue test programs for composite aircraft structural elements is proposed. For the case of uniaxial tension-compression load of laminates from layered composites representing the upper and lower panels of composite wings of transport category aircraft, a method for calculating the estimation of this parameter is proposed. It is shown that using the "equivalent stress" parameter, the following main tasks can be solved: assessment of the damage resistance of a structural element with a given program of its fatigue tests; comparison of damages resistance of various programs, calculation of equivalents between the programs; calculation of fatigue life of layered composites samples and elements using the fatigue curve under regular load. It is noted that the fundamental meaning of the proposed method for calculating the equivalent stresses and equivalents of fatigue test programs is the use of a special hypothesis of a fatigue damage accumulation rule. An example of calculating the equivalent stresses and equivalents of various modifications of the quasi-random program for CFRP T300/5208 [45/0/-45/90] 2s samples of fiber-carbon composite with the open hole is presented. The fatigue life of these samples under load with the considered modifications was calculated using the obtained values of equivalent stresses and equivalents. Good agreement between the calculated results and experimental data is shown.